A Retrospective Study on Maternal and Neonatal Outcomes of Adolescent Pregnancies at a Referral Hospital in Bengaluru - Ramegowda Chethana; Divyarajan Vinitha Kiruffi; K. S. Seema; Anwith Huluvadi Shivalingaiah (Archives of Medicine and Health Sciences)
Background and Aim: Adolescent pregnancy has become an important health and social issue in both developing and developed countries. According to the National Family Health Survey-5, the prevalence of adolescent pregnancy in India is 6.8%. Adolescent pregnancy has shown association with preterm birth, low birth weight, perinatal death, miscarriage, puerperal sepsis, mental illness, and maternal death. With this background, this study was taken up with the objective to delineate the maternal and neonatal complications seen in teenage pregnant women. Materials and Methods: This study was a retrospective case record analysis with descriptive study design of all adolescent pregnancies delivered between October 2021 and September 2022 with mother’s age being ≤19 years, at a first referral hospital in Bengaluru were included in the study. Participants who could not be contacted were excluded from the study. Results: Out of the 1005 deliveries during the study period, 55 were adolescent pregnancy with a proportion of 5.47%. The most common maternal complication is pregnancy-induced hypertension (8.5%) and the most common neonatal complication is low birth weight (21.2%). Conclusions: Despite continuous and consistent efforts by the health-care administration and health-care personnel under maternal and child national health program, the expected outcomes in terms of usage of contraception and delaying first pregnancy have not been attained.